Role of Drug-metabolizing Enzymes in Cancer and Cancer Therapy - Feng, Siqi; Li, Anqi; Zheng, Yi-Chao; Liu, Hong-Min (Current Drug Metabolism, 2020)
Background: Cancer is one of the most serious diseases threatening human health with high morbidity and mortality in the world. For the treatment of cancer, chemotherapy is one of the most widely used strategies, for almost all kinds of tumors and diverse stages of tumor development. The efficacy of chemotherapy not only depends on the activity of the drug administrated but also on whether the compound could reach the effective therapeutic concentration in tumor cells. Therefore, expression and activity of drug-metabolizing enzymes (DMEs) in tumor tissues and metabolic organs of cancer patients are important for the dispositional behavior of anticancer drugs as well as the clinical response of chemotherapy. Methods: This review summarizes the recent advancement of the DMEs expression and activity in various cancers, as well as the potential regulatory mechanisms of major DMEs in cancer and cancer therapy. Results: Compared to normal tissues, expression and activity of major DMEs are significantly dysregulated in patients by various factors including epigenetic modification, ligand-activated transcriptional regulation and signaling pathways. Additionally, DMEs play an important role in anticancer drug efficacy, chemoresistance as well as the activation of prodrugs. Conclusion: This review reinforces a more comprehensive understanding of DMEs in cancer and cancer therapy, and provides more opportunities for cancer therapy.
Keywords: Drug-metabolizing enzymes